Do varão casado a um reino virtuoso (Portugal - sécs. XIV-XVI) - Teodoro, Leandro Alves [UNESP] (2014)
In legal, chronic and treaty works, in general, but mainly in the manuals and treaties of confession produced in Portugal since the late fourteenth century to the early sixteenth century, there are several guidelines on how men should act and behave within their homes. In these guidelines are being drawn, in some details, the various aspects of what was and what should be the married life, permiting thus perceive that marital sphere was interpreted as a kind of guiding from the other spheres of the existence of Christians. Marriage, after a long process, stands as one of the main bases of the social order, so that the conjunct of the desired qualities to the man journeyed the context of married life, but aimed to focus far beyond it. Emphasizing therefore the precepts and rules established by laic scholars and fifteenth confessors to their contemporaries, the aim of this study is to scrutinize the virtues , attitudes, behaviors, and care duties outlined as ideal in the court of Avis and Portuguese bishoprics as well as examine how the use of the sacraments of Penance and Matrimony as master keys to teach men the right way to lead their kingdom and family